'Real-life' information on pulmonary arterial hypertension: the iPHnet Project. (December 2014) - Poscia, Roberto; Ghio, Stefano; D'Alto, Michele; Vitulo, Patrizio; Mulè, Massimilano; Albera, Carlo; Parisi, Francesco; Badagliacca, Roberto; Fedele, Francesco; Vizza, Carmine Dario
Abstract Background: Over the last two decades the development and analysis of a number of registries have enhanced the knowledge of the epidemiology, presentation, natural history, and pathophysiology of pulmonary arterial hypertension (PAH). The understanding of the effectiveness of available treatments has also been greatly improved. However, most of the registries present some methodological issues, such as differences in the classification of patients and presence of confounding factors or missing values, that can impact on the generalizability of the results. Objective: The aim of this study is to present the Italian Pulmonary Hypertension Network (iPHnet) Project, a database used to collect health records on patients with PAH that can also be used for research purposes to retrieve ad hoc information. Results: iPHnet presents various characteristics such as facilitated access, data sharing and interoperability, update, patient's anonymity and data integrity. The system also enables the creation of patients' electronic health records (EHRs), the exportation and personalization of data and the possibility to design clinical report forms (CRFs) and collect information usable in clinical trials. In addition, it is possible to analyze the information present in the registry, creating graphs or other immediately available charts to evaluate the trends of a specific data and perform therapeutic or clinic adjustments. Treatment of data in the iPHnet database complies with FDA requirements, backup and disaster recovery policies and patients' privacy. Conclusions: iPHnet is a flexible tool that integrates the capabilities of an EHR for PAH patients with those of a PAH registry. The ability to retrieve relevant information – although with all the limitations of any registry-based analysis – and to create appropriate CRFs will facilitate the development of prospective and retrospective trials aimed at providing new 'real-life' evidence on PAH.